FROM THE PHOTOVOLTAIC EFFECT TO A LOW VOLTAGE PHOTOVOLTAIC GRID CHALLENGE – A REVIEW (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
The paper investigates the progress of on-grid photovoltaic systems in Romania, particularly in the residential and commercial sectors. Emphasizing the financial stability offered by on-grid systems, the study underscores the predictability of solar production and the support from governmental incentives. The graphs and tables presented contain processed data from studies carried out by the governmental authorities. This research acknowledges the pivotal role of photovoltaic cell advancements in enhancing the efficiency and accessibility of on-grid systems. However, the swift expansion of solar capacity raises concerns regarding its impact on low-voltage power transmission grids, leading to fluctuations that may compromise electricity quality. Grid flexibility and battery integration are proposed to address these challenges, recognizing their potential benefits alongside associated costs and technical complexities. The central theme revolves around managing the transition towards sustainable and efficient energy infrastructure in Romania.
Keywords: Photovoltaic cell; Development; Photovoltaic systems; Prosumers; Grid challenges; Possible solutions